Spectrum of K ras mutations in Pakistani colorectal cancer patients - Murtaza,B.N. (2014)
The incidence of colorectal cancer (CRC) is increasing daily worldwide. Although different aspects of CRC have been studied in other parts of the world, relatively little or almost no information is available in Pakistan about different aspects of this disease at the molecular level. The present study was aimed at determining the frequency and prevalence of K ras gene mutations in Pakistani CRC patients. Tissue and blood samples of 150 CRC patients (64% male and 36% female) were used for PCR amplification of K ras and detection of mutations by denaturing gradient gel electrophoresis, restriction fragment length polymorphism analysis, and nucleotide sequencing. The K ras mutation frequency was found to be 13%, and the most prevalent mutations were found at codons 12 and 13. A novel mutation was also found at codon 31. The dominant mutation observed was a G to A transition. Female patients were more susceptible to K ras mutations, and these mutations were predominant in patients with a nonmetastatic stage of CRC. No significant differences in the prevalence of K ras mutations were observed for patient age, gender, or tumor type. It can be inferred from this study that Pakistani CRC patients have a lower frequency of K ras mutations compared to those observed in other parts of the world, and that K ras mutations seemed to be significantly associated with female patients.